Organoleptic Quality of Beef Meatballs Substituted with Tuna Fish Meat (Thunnus Sp) - Fransiskus Kelvin Renwarin; Nafly Comilo Tiven; Isye Jean Liur (CV. Rayyan Dwi Bharata, 2002)
This study aims to determine the organoleptic quality of beef meatballs substituted with tuna meat. Beef (Biceps femoris muscle) and tuna (Thunnus sp) fillet portion, each mashed separately, for making meatballs with a composition of 70% beef, 16% tapioca flour, 9% ice water , 2% salt, and 3% spices consisting of garlic 2,2% and 0.8 ground pepper. The beef was substituted with tuna meat at a level of 0%, 20% and 40%, then all the ingredients were finely ground until they were evenly mixed to form a dough. The dough was shaped round (± 2 cm) manually by hand, then boiled until cooked (until the meatballs float), then tested organoleptically using untrained panelists. The variables observed were color, smell, elasticity, texture and taste of meatballs. The data obtained were analyzed for variance with a completely randomized design, with 3 treatments, namely P0 (beef without being substituted with tuna meat), P1 (beef substituted 20% with tuna meat), P2 (beef substituted 40% with beef). tuna fish). If there are differences between treatments, further tested with Duncan's test. The results showed that the substitution of beef meatballs with tuna meat had no significant effect on the color, smell, elasticity, texture and taste of beef meatballs.